Adherence to statin treatment and associated factors in female users from the Unified Health System (SUS) - Bonfim, Mariana Rotta; Hansen, Arina; Turi, Bruna Camilo; Zanini, Gabriel De Souza; Oliveira, Acary Souza Bulle; Amaral, Sandra Lia Do; Monteiro, Henrique Luiz [UNESP] (Universidade de São Paulo, Escola de Enfermagem, 2014)
Objective: To identify the adherence rate of a statin treatment and possible related factors in female users from the Unified Health System. Method: Seventy-one women were evaluated (64.2 ± 11.0 years) regarding the socio-economic level, comorbidities, current medications, level of physical activity, self-report of muscular pain, adherence to the medical prescription, body composition and biochemical profile. The data were analyzed as frequencies, Chi-Squared test, and Mann Whitney test (p<0.05). Results: 15.5% of women did not adhere to the medical prescription for the statin treatment, whose had less comorbidities (p=0.01), consumed less quantities of medications (p=0.00), and tended to be younger (p=0.06). Those patients also presented higher values of lipid profile (CT: p=0.01; LDL-c: p=0.02). Musculoskeletal complains were not associated to the adherence rate to the medication. Conclusion: The associated factors to adherence of dyslipidemic women to statin medical prescription were age, quantity of comorbidities and quantity of current medication.

Objetivo: Identificar la tasa de adherencia al tratamiento con estatinas y los posibles factores relacionados en usuarias del Sistema Único de Salud. Métodos: Fueron evaluadas 71 mujeres (64,2 ± 11,0 años) según nivel socioeconómico, comorbilidades, uso de medicamentos, nivel de actividad física, dolor muscular autoinformado, adherencia a la prescripción médica, composición corporal y perfil bioquímico. Los datos fueron analizados por frecuencia, test de chi-cuadrado y la prueba de Mann- Whitney (p<0,05). Resultados: El 15,5% de las mujeres no se adhirieron a la prescripción médica para el tratamiento con estatinas, éstas tenían menos comorbilidades (p=0,01), consumían menos cantidad de medicamentos (p=0,00) y presentaban tendencia a ser más jóvenes (p=0,06). Además, estas pacientes presentaron valores mayores en el perfil lipídico (CT: p=0,01, LDL-C: p=0,02). La referencia de dolor musculoesquelético no se asociaron con la tasa de adherencia al medicamento. Conclusión: Los factores asociados con la adherencia de las mujeres con dislipidemia a la prescripción de estatinas fueron la edad, el número de comorbilidades y el número de medicamentos.
Aderência ao tratamento por estatinas e fatores associados em usuárias do Sistema Único de Saúde
Adherencia al tratamiento con estatinas y factores asociados en usuarias del sistema unico de salud de brasil
Keywords: Hydroxymethylglutaryl-CoA Reductase; Inhibitors; Dyslipidemias; Health profile; Medication adherence; Public health; Inibidores de Hidroximetilglutaril-CoA; Redutases; Dislipidemias; Perfil de saúde; Adesão à medicação; Saúde pública